2004
DOI: 10.1088/0953-8984/16/48/053
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering studies on ZnO doped with Ga and N (codoping), and magnetic impurities

Abstract: ZnO layers doped simultaneously with Ga and N (codoping), and magnetic elements (V, Co) were characterized by Raman scattering to study their structural stability. Five impurity modes were observed in range 200-900 cm −1 in the doped samples, and showed characteristic variation with the doping level. It is shown that these modes can be used as a good measure of lattice defects induced by doping. The Raman spectra showed that the magnetic elements were incorporated up to 5 mol% without serious deterioration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 15 publications
4
32
0
Order By: Relevance
“…Also, the dominant mode in the disordered region appears to be closer to 550 cm -1 vice 522 or 580 cm -1 . These findings are quite similar to reports of Raman spectra in Zn 1-x Co x O which does exhibit the ferromagnetic behavior [21] crystals were grown by a modified meltgrowth technique described elsewhere [13]. Varying doping levels of Mn and Co were incorporated into the ZnO crystals during the growth process by varying the ratio of transition metal oxide to zinc oxide within the precursor boule.…”
Section: Resultssupporting
confidence: 87%
“…Also, the dominant mode in the disordered region appears to be closer to 550 cm -1 vice 522 or 580 cm -1 . These findings are quite similar to reports of Raman spectra in Zn 1-x Co x O which does exhibit the ferromagnetic behavior [21] crystals were grown by a modified meltgrowth technique described elsewhere [13]. Varying doping levels of Mn and Co were incorporated into the ZnO crystals during the growth process by varying the ratio of transition metal oxide to zinc oxide within the precursor boule.…”
Section: Resultssupporting
confidence: 87%
“…9 Also, the correlation between N concentration and the intensity of the additional peaks has been confirmed by some works 8,10 and contradicted by others. 9 In a recent study, 10 on the basis of a local phonon density of states calculation, it was suggested that the additional mode observed at 275 cm −1 originates from localized vibration of the Zn atoms in a first-neighbor environment where part of the O atoms are replaced by N atoms. No experimental evidence of the participation of N atoms in the LVM observed in N-doped ZnO has been given so far.…”
mentioning
confidence: 89%
“…Rigid Ion Model Parameters for ZnO (All parameters are in units of N·cm −1 , except for Z which is an effective charge, a number.) [4] 522.0 [10] 514.9 Present and eigenvectors, and the defect mode is identified from the eigenvector, as usual. The Kellerman parameters determined by the rigid ion model are given in Table II.…”
Section: Molecular Modelmentioning
confidence: 99%
“…In addition to Dietl's prediction, ferromagnetism (FM) in magnetically doped ZnO has been theoretically investigated by ab initio calculations based on the local density approximation [2]. Although reviews are available for bulk and nano-ZnO doped with magnetic impurities like Co and V [4], very few reports are available for ZnO doped with manganese [5]. Sharma et al [2] have carried out measurements on ZnO:Mn for the FM transition.…”
Section: Introductionmentioning
confidence: 99%